THE SPECIFIC FEATURES OF AGILITY IN PRESCHOOL CHILDREN - Abdurafik Bobomurodov Egamurodovich (Research Focus International Scientific Journal, 2025)
According to the Resolution of the President of the Republic of Uzbekistan dated December 29, 2016 No PP 2707 "On measures to further improve the system of preschool education in 2017-2021", September 30, 2017 No PP-3305 on the organization of the Ministry of Preschool Education of the Republic of Uzbekistan emerging, new approaches in the preschool education system require the emergence of new types of issues, the creation of scientific research and new projects in this area [1,2]. Preparation of children aged 5-6 for school education in preschool institutions in accordance with paragraph 2 of the Decree of the President of the Republic of Uzbekistan "On measures to further improve the system of preschool education in 2017-2021" It is planned to carry out planned work on the establishment of 6,100 short-term groups [3]. Considering above-mentioned facts, this article covers the specific features of agility in preschool children and the issues of development taking into account its variation in accordance with their ages.